The Role of Coping and Ethnolinguistic Vitality in Predicting Franco-Ontarian Adolescents’ Perceived Stress - Gallitto, Elena; Montgomery, Cameron (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2022)
This study investigated the predictive effects of ethnolinguistic vitality and coping strategies on perceived stress in a sample of 267 Canadian adolescents aged 15 to 18 years. An exploratory factor analysis was performed to extract the factors to be used in the regression analysis. For ethnolinguistic vitality, Anglophone language vitality and Francophone language vitality, shopping and media use in English and bilingual identity were extracted. Coping was factored into three main factors: Adaptive Coping, Maladaptive Coping and Seeking Social Support. Adolescents’ perceived stress converged into two main factors: Stress Vulnerability and Self-Distrust. Regression results indicated that adaptive coping strategies predicted lower levels of stress vulnerability and self-distrust, whereas maladaptive coping predicted increased levels of these stress factors. Moreover, Anglophone and Francophone language vitality predicted lower levels of adolescents’ stress vulnerability above and beyond the effects of coping strategies. These findings attest to the importance of ethnolinguistic vitality in contributing to adolescent well-being.